The Effect of Foot Reflexology on the Sexual Function of Lactating Women: A Randomized Clinical Trial - Ghanbari, Zahra; Valiani, Mahboubeh; Kohan, Shahnaz (Reviews on Recent Clinical Trials, 2025)
Introduction Sexual health is an essential part of women's lives at different ages. Pregnancy, childbirth, and breastfeeding can affect women's sexual function by inducing biological, psychological, and social changes. Due to the prevalence of sexual dysfunction in lactating women and the effects of reflexology therapies on it, this study was conducted to investigate the effect of foot reflexology on the sexual function of lactating women. Materials and Methods This randomized clinical trial was conducted in selected health centers of Isfahan in 2022 on 64 lactating women (32 women in each group of intervention and control). The samples were selected using the convenience sampling method and were randomly divided into two groups with a random number table. Each participant in the intervention group received 10 sessions of foot reflexology, and each session lasted for 50 minutes (25 minutes for each foot) and was held every three days. The Female Sexual Function Index (FSFI) questionnaire was completed before the intervention and four weeks after the end of it. The control group received routine care and completed the questionnaire before the intervention and 9 weeks later. Data were analyzed using SPSS version 20 and independent/paired t-tests. Results Data analysis showed that the subjects of the two groups were homogeneous in demographic and fertility characteristics at the beginning of the study. The total mean score of sexual function in the intervention group was 20.36 ± 4.16 before the intervention and 28.05 ± 2.89 after the intervention. In the control group, this score was 20.51 ± 3.75 before the intervention and 20.54 ± 3.71 nine weeks after it. A comparison of the total mean score of sexual function and dimensions showed a significant difference between the two groups four weeks after the intervention (p <0.001). In the intervention group, significant changes were observed in the total mean score of sexual function and its dimensions four weeks after the intervention compared to before the intervention. However, in the control group, there were no significant changes in this score and its dimensions nine weeks later compared to before the intervention. Conclusion Based on the results of this study, lactating women in the two groups did not have a desirable sexual function before the intervention. However, foot reflexology in the present study could effectively improve the sexual function of women in the reflexology group. Therefore, it is recommended to employ foot reflexology therapy in health centers to help lactating women restore their sexual function. Clinical Trial Registration Number IRCT20210814052180N1.
Keywords: sexual function